If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5-6(4p+4)=-29
We simplify the equation to the form, which is simple to understand
-5-6(4p+4)=-29
Reorder the terms in parentheses
-5+(-24p-24)=-29
Remove unnecessary parentheses
-5-24p-24=-29
We move all terms containing p to the left and all other terms to the right.
-24p=-29+5+24
We simplify left and right side of the equation.
-24p=0
We divide both sides of the equation by -24 to get p.
p=-0
| x^4+10x^2-11= | | 14p^2-72+64=0 | | 3xy+2xy-xy=0 | | 5-c/3 | | 2(x-3)+4(x+4)=28 | | -75+7.5x=150 | | 7/5x=-1 | | m-23/5-7m-22/6=1 | | 3x^2+30x-7=0 | | -15x+5-4(x-1)=-4x-(14x-4)+4 | | 4-0.4(f-12)=0.5(7f-12) | | 104-6c=440 | | 2(h-414)=692 | | q=4p+8 | | 2*1/(2√x)-1=0 | | 6h+18=48 | | 8(q+2)=96 | | 6-0.5(y-1)=0.7(4y-1) | | 6(n+5)=12 | | (11b-6)-5(2b+1)=-2 | | 11(x)-6=-336 | | 3[9(x+4)+2(x+1)]=0 | | 7(m-81)=84 | | 5(g-73)=95 | | 2(y+2)(x-3)(1-y)=0 | | 0.9-0.5y=4.4 | | x(b-3)=0 | | (11b-6)-5(2b+1)=2 | | 4x(x-1)-7x(x-6)=5x(x+6) | | (5u-6)(4-u)=0 | | 5(3+n)+2n=-27 | | D=1/8(h)(a-b) |